2014
DOI: 10.1088/1748-9326/9/10/105008
|View full text |Cite
|
Sign up to set email alerts
|

Reducing uncertainty in nitrogen budgets for African livestock systems

Abstract: Livestock is poorly represented in N budgets for the African continent although some studies have examined livestock-related N flows at different levels. Livestock plays an important role in N cycling and therefore on N budgets including livestock-related flows. This study reviews the literature on N budgets for Africa to identify factors contributing to uncertainties. Livestock densities are usually modelled because of the lack of observational spatial data. Even though feed availability and quality varies ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 88 publications
0
22
0
Order By: Relevance
“…All emission source categories were quantified separately for dairy cattle using a classification of livestock production systems (LPS, figure S2): mixed rainfed system in arid areas (MRA), mixed rainfed system in humid areas (MRH), mixed rainfed system in tropical highlands (MRH), mixed irrigated system in arid areas (MIA), mixed irrigated system in humid areas (MIH) and the mixed irrigated system in tropical highlands (MIT). This LPS classification, developed by Robinson et al (2011), has been used to analyse different environmental and economic aspects of livestock production , Rufino et al 2014, Thornton and Herrero 2010. GHG emissions that result from dairy concentrate supplementation, including the cultivation of feed ingredients were calculated using an emission factor from Weiler et al (2014).…”
Section: Calculating Ghg Emissions and Milk Productionmentioning
confidence: 99%
“…All emission source categories were quantified separately for dairy cattle using a classification of livestock production systems (LPS, figure S2): mixed rainfed system in arid areas (MRA), mixed rainfed system in humid areas (MRH), mixed rainfed system in tropical highlands (MRH), mixed irrigated system in arid areas (MIA), mixed irrigated system in humid areas (MIH) and the mixed irrigated system in tropical highlands (MIT). This LPS classification, developed by Robinson et al (2011), has been used to analyse different environmental and economic aspects of livestock production , Rufino et al 2014, Thornton and Herrero 2010. GHG emissions that result from dairy concentrate supplementation, including the cultivation of feed ingredients were calculated using an emission factor from Weiler et al (2014).…”
Section: Calculating Ghg Emissions and Milk Productionmentioning
confidence: 99%
“…They found that using agro-forestry systems of different tree structures near 'hot spots' of ammonia in the landscape could provide an effective abatement option for the livestock industry in livestock operations in the UK. This example may be contrasted with rather different livestock systems in low-N input Africa, where Rufino et al (2014) report how only few data are available to date to understand the livestock-related N flows. They therefore propose joint efforts for data collection and the development of a nested systems definition of livestock systems to link local, regional and continental level and to increase the usefulness of point measurements of N losses.…”
Section: Progress In Implementing Nitrogen Management Actionsmentioning
confidence: 99%
“…This makes the virtual N factor of Tanzania livestock products low compared to those in developed countries. Grass feeding does not incur large N losses as does feeding cultivated grain to cattle, but it can deplete the soil, as much of the nitrogenous waste emitted by cattle as manure is leached into the environment rather than returned to the soil (Rufino et al 2014). (2012).…”
Section: Food Production: Virtual Nitrogen Factorsmentioning
confidence: 99%